A scoping review of the use of e-learning and e-consultation for healthcare workers in low- and middle-income countries and their potential complementarity. (30th December 2021) - Ionescu, Alma; de Jong, Peter G M; Drop, Stenvert L S; van Kampen, Sanne C
Abstract: Objective: Although the provision of e-learning (EL) training for healthcare workers (HCWs) and provider-to-HCW e-consultation (EC) is considered useful for health outcomes, research on their joint use is limited. This scoping review aimed to create an overview of what is currently known in the literature about the use and implementation of EC and EL by HCWs in LMICs and to answer the question of whether there is evidence of complementarity. Materials and Methods: Scientific databases were searched and peer-reviewed papers were reviewed systematically according to predefined inclusion/exclusion criteria. Data were extracted including the study focus (EC/EL), year of publication, geographical location, target population, target disease(s) under study, type(s) of study outcomes, and article type. Results: A total of 3051 articles were retrieved and screened for eligibility, of which 96 were kept for analysis. Of these, only 3 addressed both EL and EC; 54 studies addressed EL; and 39 addressed EC. Most studies looked at gain in knowledge/skills usability, efficiency, competence, and satisfaction of HCW, or barriers/challenges to implementation. Descriptive studies focused on the application of EL or EC for targeting specific health conditions. Factors contributing to the success of EC or EL networks were institutional anchoring, multiple partnership, and capacity building of local experts. Conclusions: Our review found an important gap in the literature in relation to the complementary role of EL and EC for HCWs in LMICs evidenced by outcome measures. There is an important role for national and international academic institutions, learned medical societies, and networks to support regional experts in providing EL and EC for added value that will help the clinical performance of HCWs and improve health outcomes.